Pemahaman teori pendidikan dalam konteks pendidikan kontemporer: Sebuah kajian literatur - Maulida, Ikrima; Lestari, Eci Anita; Sari, Cut Kumala (Yayasan Mitra Persada Nusantara, 2024)
The aim of this research is to examine various educational theories that have developed over time and their relevance in the contemporary educational context. This research uses a document study or literature study method by analyzing various sources such as books, journals and articles related to educational theory. This research focuses on major educational theories, such as behavioral theory, constructivism, humanism, and critical and sociocultural theory, and how each theory contributes to the development of the modern education system. The results of the analysis show that each educational theory has different but complementary basic principles, and each provides a relevant approach to facing educational challenges in this digital era. Behavioral theory places greater emphasis on measuring learning outcomes through positive reinforcement, while constructivism encourages experience-based learning and problem solving. The humanistic approach emphasizes the development of individual potential, while critical and sociocultural theories encourage education to become a tool for social transformation. The conclusion of this research is that the application of various educational theories must be adapted to the needs of students, social context, and technological developments to create effective and relevant learning experiences.